Remifentanil Promotes PDIA3 Expression by Activating p38MAPK to Inhibit Intestinal Ischemia/Reperfusion-Induced Oxidative and Endoplasmic Reticulum Stress - Shen, Jiantong; Zhan, Yaqing; He, Qiulan; Deng, Qiwen; Li, Kunhe; Wen, Shihong; Huang, Wenqi (Frontiers in Cell and Developmental Biology, 2022)
Background. Remifentanil protects against intestinal ischemia/reperfusion (I/R) injury; however its exact mechanism remains to be elucidated. The objective of this study was to investigate the underlying molecular mechanism of remifentanil in intestinal I/R injury in mice. Methods. We evaluated the intestine-protective effect of remifentanil in adult male mice with 45 min superior mesenteric artery (SMA) occlusion followed 4 h reperfusion by determining the following: intestinal Chiu’s scores, diamine oxidase (DAO), and intestinal fatty acid binding protein (iFABP) in serum; the apoptotic index, lipid peroxidation product malondialdehyde (MDA), and superoxide dismutase (SOD) activity in the intestinal mucosa; and the intestinal mRNA and protein expressions of Bip, CHOP, Caspase-12, and cleaved Caspase-3, reflecting endoplasmic reticulum (ER) stress. Furthermore, conditional knockout (cKO) mice, in whom the protein disulfide isomerase A3 (PDIA3) gene was deleted from the intestinal epithelium, and SB203580 (a selective p38MAPK inhibitor) were used to determine the role of PDIA3 and p38MAPK in I/R progression and intestinal protection by remifentanil. Results. Our data showed that intestinal I/R induced obvious oxidative stress and ER stress-related cell apoptosis, as evidenced by an increase in the intestinal mucosal MDA, a decrease in the intestinal mucosal SOD, and an increase in the apoptotic index and the mRNA and protein expression of Bip, CHOP, Caspase-12, and cleaved Caspase-3. Remifentanil significantly improved these changes. Moreover, the deletion of intestinal epithelium PDIA3 blocked the protective effects of remifentanil. SB203580 also abolished the intestinal protection of remifentanil and downregulated the mRNA and protein expression of PDIA3. Conclusion. Remifentanil appears to act via p38MAPK to protect the small intestine from intestinal I/R injury by its PDIA3-mediated antioxidant and anti-ER stress properties.